ChemInform Abstract: Lewis Acid‐Mediated Azidolysis of 2, 3‐Three Membered Heterocyclic Amines. Issue 9 (4th March 2014) - Righi, Giuliana; Scotti, Giorgio; Caruso, Francesco; Rossi, Miriam; Mecozzi, Francesco; Antonioletti, Roberto; Pelagalli, Romina
Abstract The regioselectivity of the described azidolysis of aziridines and epoxides can be controlled by the use of different Lewis‐acids.